2013
DOI: 10.5935/0946-5448.20130017
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus in adolescents and its relation to the use of personal sound systems

Abstract: Introduction: References to recreational exposure to high sound pressure levels (SPL) and the risk of hearing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a prior study conducted by Fitri Sakinah 14 regarding the frequency of earphone use, the result was that 78.9% of respondents used earphones 1-4 days/week and 21.1% used ear phones >5 days/week. On the other hand, a research conducted by Silvestre et al 15 in 2013 showed that 74.43% of respondents used earphones >5 days/ week. This discrepancy could be caused by using the earphones not for a long period or continuously at a relatively low volume or intensity.…”
Section: Discussionmentioning
confidence: 97%
“…In a prior study conducted by Fitri Sakinah 14 regarding the frequency of earphone use, the result was that 78.9% of respondents used earphones 1-4 days/week and 21.1% used ear phones >5 days/week. On the other hand, a research conducted by Silvestre et al 15 in 2013 showed that 74.43% of respondents used earphones >5 days/ week. This discrepancy could be caused by using the earphones not for a long period or continuously at a relatively low volume or intensity.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that the loud sound associated with physical activity releases adrenaline, which generates pleasure, 24 and often there lies the justification for children, adolescents, and young adults to expose themselves to amplified music and other noises in their day-to-day activities. 25 As for education, studies say that the lower the education, the lower the capacity of reality perception. The students of the YAE are largely people who chronologically returned to study outside the conventional timeframe.…”
Section: Discussionmentioning
confidence: 99%